A90V TDP-43 Variant Results in the Aberrant Localization of TDP-43 In Vitro - Winton, Matthew J. (2008)
TAR DNA-binding protein-43 (TDP-43) is a highly conserved, ubiquitously expressed nuclear protein that was recently identified as the disease protein in frontotemporal lobar degeneration with ubiquitin positive inclusions (FTLD-U) and amyotrophic lateral sclerosis (ALS). Pathogenic TDP-43 gene (TARDBP) mutations have been identified in familial ALS kindreds, and here we report a TARDBP variant (A90V) in a FTLD/ALS patient with a family history of dementia. Significantly, A90V is located between the bipartite nuclear localization signal sequence of TDP-43 and the in vitro expression of TDP-43-A90V led to its sequestration with endogenous TDP-43 as insoluble cytoplasmic aggregates. Thus, A90V may be a genetic risk factor for FTLD/ALS because it predisposes nuclear TDP-43 to redistribute to the cytoplasm and form pathological aggregates.